Hot Oil Exposure on Styrofoam and Black Crackle Bag Effect on Malondialdehyde MDA Level of White Rat (Rattus norvegicus) Wistar Strain - Marcella; Simanjuntak, Kristina; Yuni Setyaningsih (Talenta Publisher, 2020)
ABSTRACT This study purposed to determine the effect of hot oil exposure on styrofoam and black plastic bag on MDA levels in rats. The study was purely experimental, a sample of 28 Wistar rats, weight Â±200gram, age 3 months, divided into 4 groups, treatment was given for 28 days. Negative control was given feed and drink; styrofoam group was given feed, drink, oil on styrofoam; the black plastic group was given feed, drink, oil on black plastic; positive control was given feed, drink, toluene mixed oil. On 14th and 28th-day blood was taken from the tail and examined for plasma MDA by spectrophotometer Î»=532nm. One-way ANOVA shows there is an effect of hot oil exposure on styrofoam and black plastic on MDA levels on the 14th and 28th days (p=0.000). Post hoc showed the styrofoam group had a significant increase in MDA levels on 14th (p=0.003) and 28th (p=0.043) compared to negative controls, the black plastic group as well on 14th (p=0.000) and 28th (p=0.000). MDA levels between styrofoam and black plastic groups significantly different on 14th (p=0.012), but not on 28th (p=0.340). There was a significant MDA increase in the styrofoam group between 14th and 28th days (p=0.009), and in the black plastic group (p=0.031). This shows that hot oil exposure on styrofoam and black plastic cause cell oxidative stress. Keyword: Black Plastic Bag, MDA, Oxidative Stress, Styrofoam ABSTRAK Penelitian bertujuan mengetahui pengaruh paparan minyak panas pada stirofoam dan kresek hitam terhadap kadar MDA. Penelitian merupakan eksperimental murni, sampel 28 ekor tikus putih galur Wistar, berat badan Â±200gram, usia 3 bulan, dibagi menjadi 4 kelompok, perlakuan selama 28 hari. Kontrol negatif diberi pakan biasa dan air minum; kelompok stirofoam diberi pakan, minum, dan minyak pada stirofoam; kelompok kresek hitam diberi pakan, minum, dan minyak pada kresek hitam; kontrol positif diberi pakan, minum, dan minyak dicampur toluene. Mengambil darah dari vena ekor pada hari ke-14 dan ke-28 lalu memeriksa MDA plasma dengan spektrofotometer Î»=532 nm. Hasil One-way Anova menunjukkan peningkatan MDA kelompok stirofoam dan kresek hitam hari ke-14 dan ke-28 (p=0.000). Uji post hoc menunjukkan MDA kelompok stirofoam meningkat signifikan pada hari ke-14 (p=0.003) dan ke-28 (p=0.043) dibanding kontrol negatif, begitu juga kelompok kresek hitam hari ke-14 (p=0.000) dan ke-28 (p=0.000). Kadar MDA antara kelompok stirofoam dan kresek hitam berbeda signifikan pada hari ke-14 (p=0.012), tetapi tidak pada hari ke-28 (p=0.340). MDA berbeda bermakna antara hari ke-14 dan ke-28 pada kelompok stirofoam (p=0.009) dan kelompok kresek hitam (p=0.031). Hal ini menunjukkan paparan minyak panas pada stirofoam dan kresek hitam dapat menimbulkan stres oksidatif sel. Kata Kunci: Kresek Hitam, MDA, Stirofoam, Stres Oksidatif